Evaluation the Risk Factors to Associate with Subsequent Epilepsy in the Children with Febrile Seizures at Tertiary Care Hospital - Sana Ilyas, Asif Abrar, Muhammad Masood Tahir, Ayesha Akram, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: This study was conducted to evaluate the risk factors of recurrence and development of epilepsy in children with febrile seizures at Nishtar Hospital Multan. Methodology: This retrospective study was conducted at Pediatrics Department of Nishtar Hospital Multan from April 2021 to April 2023. A total of 100 children with febrile seizures being follow-up for at least 1 year were included in the study. All patients whose guardians reported more two occurrences of febrile seizures, complex febrile seizures and an episode of febrile seizure with neurodevelopmental delay underwent electroencephalogram. Children with ≥2 unprovoked seizures after febrile seizure occurrence and those with an unprovoked seizure showing epileptiform discharges as detected on an EEG were suspected for development of epilepsy. Results: The results showed that FS recurrence was significantly associated with type of seizure(p<0.001) and family history of epilepsy (p=0.030). Logistic regression analysis revealed that patients who suffered from a seizure after one hour of developing a fever had a 7 times greater chance of recurrence and those with longer episodes had 3 times more risk. Patients who had a FS onset at younger than 1 year were 18 folds more likely to develop epilepsy and 10 folds in those with longer seizure duration. Conclusion: In conclusion, younger than 1-year, complex seizures, seizures within 1 hour of fever, low fever before FS onset and family history are significant risk factors of FS recurrence in children with febrile seizures. Development of epilepsy in such patients is significantly associated with FS onset at younger than 12 months of age, longer seizure duration, clonic seizures, neurodevelopmental delay, abnormal EEG, recurrent FS and complex FS. Keywords: Subsequent Epilepsy, Children, Febrile Seizures, Tertiary Care Hospital, epilepsy.